The Differences in Risk Perception between Millennials and Baby Boomers in Online Transactions - Dipa Mulia (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to distinguish the risks perceived by the millennial generation and the risks perceived by baby boomer generations when transacting online. The number of samples used in this study was one hundred thirty-five respondents. Criteria for respondents are people who have done online transactions in the generation being studied. This study uses a discriminant analysis conducted by a study of three types of risk perceived by respondents, product risk, financial risk, and shipping risk. The result showed there are statistically significant differences in the risks perceived by the millennial generation and the baby boomer generation.